THE ROLE OF AZERBAIJAN OIL IN “ NOBEL BROTHERS’ “ LIFE - Mirzayeva, Tarana (European Scientific Journal, ESJ, 2014)
The detailed information was given about the famous â€œNobel Brothersâ€ who invested capital to having fertile oil reserves Azerbaijan in XIX century in the text. As it is known,possessing oil deposit of Azerbaijan attracted the attention of foreign investors. The investors became the oil magnats of the periods thanks to Azerbaijan oil getting a large amount of oil capitals. One of such oil magnats was â€œNobel Brothersâ€ by origin Swiss. The Nobels were four brothers. Emil, Ludvig, Robert and Alfred Nobel. In 1875 the Nobels founded their own company buying a little area,and then turned this company to the â€œNobel Brothers Oil Production Societyâ€ company in 18 may 1879. The activities of company involved almost all spheres of oil industry:oil research, production, refining, transportation etc. â€œNobel Brothersâ€ got leadership for developing of oil industry in Baku thanks to strong competition. Especially, in Russian bazaar they possessed representatives and depots for the purpose of transportation of much needed gas field in some cities of Russia(Charchin, Saratov, Babrusk, Nizhny-Novgorod, Perm etc.), as well as, in various Europe cities (Geneva, Hamburg, London and Manchester etc.) â€œNobel Brothersâ€ worked for achieving significant success in all directions of oil business consulting with outstanding oil-chemists scientists (D.I.Mendeleyev, K.I.Lisenko, L.Q.Qurvich and engineers A.V.Bari, V.Q.Shuchov and others). As a result, â€The Nobel Brothersâ€ signed very important innovations in the world oil history. Life of â€œNobel Brothersâ€ was studied in different years investigated. Today those studies are being continued by Azerbaijan and Swedish scientists. For instance, the book â€œThe Nobels and Baku Oilâ€, information, unique photos and documents were reflected about genealogical tree of the Nobels, activities in 1830-1860 in Russia, 1874-1920 in Azerbaijan.